1993
DOI: 10.1128/mcb.13.2.961-969.1993
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation by Simian Virus 40 Large T Antigen: Interactions with Multiple Components of the Transcription Complex

Abstract: Simian virus 40 (SV40) large T antigen is a potent transcriptional activator of both viral and cellular promoters. Within the SV40 late promoter, a specific upstream element necessary for T-antigen transcriptional activation is the binding site for transcription-enhancing factor 1 (TEF-1). The promoter structure necessary for T-antigen-mediated transcriptional activation appears to be simple. For example, a promoter consisting of upstream TEF-1 binding sites (or other factor-binding sites) and a downstream TAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To overcome this limitation, mammalian DNA tumor viruses encode proteins that interact with components of the host transcriptional apparatus and cell cycle regulatory network (Nevins, 1992). They target basal transcription factors (Gruda et al ., 1993), the histone transacetylase p300 (Eckner et al ., 1994), and the tumor suppressors, pRb (Dyson et al ., 1992) and p53 (Werness et al ., 1990). These protein interactions cause quiescent animal cells to re‐enter the cell division cycle and synthesize the enzymes necessary for viral DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this limitation, mammalian DNA tumor viruses encode proteins that interact with components of the host transcriptional apparatus and cell cycle regulatory network (Nevins, 1992). They target basal transcription factors (Gruda et al ., 1993), the histone transacetylase p300 (Eckner et al ., 1994), and the tumor suppressors, pRb (Dyson et al ., 1992) and p53 (Werness et al ., 1990). These protein interactions cause quiescent animal cells to re‐enter the cell division cycle and synthesize the enzymes necessary for viral DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…The open region contains binding sites for numerous trans-acting factors that stimulate transcription from the late promoter (6,7,(28)(29)(30)(44)(45)(46)(47)(48)(49). In order to gain insight into mechanisms by which trans-acting factors function, we determined the level of occupancy of several trans-acting factor binding sites in the VTC origin region.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that T-antigen is absent from the origin site in the elongation complex, a finding that was inconsistent with certain models for the role of T-antigen in the control of transcription. This in turn spurred efforts to evolve alternative models for the participation of T-antigen in late transcription (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of TEF-1 in a variety of cells resulted in squelching of transcriptional activity (2,7,8,24), suggesting that other limiting transcriptional co-activators are required for TEF-1 transactivation functions. We and others subsequently found that TEF-1 can interact with TBP (6,24,25), an essential component of the basal transcription machinery, and prevent TBP binding to the TATA box (24). These findings provide one mechanism by which TEF-1 may negatively regulate gene expression.…”
mentioning
confidence: 77%
“…These homologues are derived from separate genes, and the individual products are expressed differentially in a variety of tissues (1)(2)(3)(4)(5). Initially TEF-1 was identified as a 53 kDa HeLa protein required for SV40 early gene transcription (1), which is mediated by TEF-1 binding to the GT-IIC and SphI/SphII enhansons associated with the SV40 early gene enhancer (2,6,7). Subsequent studies proved TEF-1 is a ubiquitous factor implicated in directing the expression of a wide variety of genes, including human papillomavirus-16 E6 and E7 oncogene transcription (8), murine cardiac and skeletal muscle-specific gene expression (9)(10)(11)(12)(13), and early gene expression in mouse development (14).…”
mentioning
confidence: 99%